Enhancing Critical Thinking and Short Story Writing Skills in Senior High School Students Through the Guided Inquiry Model - Meliya Wati; Ade Hikmat; Herri Mulyono (AL-ISHLAH: Jurnal Pendidikan, 2025)
Writing is a complex and essential language skill that integrates cognitive, linguistic, and creative elements. Many students face challenges in developing writing process skills and critical thinking, particularly in short story composition. This study investigates the effectiveness of the guided inquiry learning model in enhancing students' writing process skills and critical thinking abilities. A true experimental design with a randomized control group was employed, involving two groups of 11th-grade students from SMA Negeri 4 Pandeglang (N = 64). The experimental group received instruction using the guided inquiry model, while the control group followed conventional methods. Data were collected through tests, observation sheets, documentation, and interviews. Students’ critical thinking skills were measured using a validated post-test and analyzed with the Independent Sample T-Test in SPSS 22. The results showed a progressive increase in the writing process skills of students in the experimental group across three meetings, with an overall average score of 76.46%, categorized as “good.” Additionally, the critical thinking post-test revealed a statistically significant difference between the experimental and control groups (p = 0.0015, one-tailed), indicating the positive impact of guided inquiry learning on students' higher-order thinking. The guided inquiry model effectively enhances students’ short story writing process skills and significantly improves their critical thinking abilities. This model is recommended as an alternative instructional strategy for developing literacy and cognitive skills in secondary education.